Distinct hybridization modes in wide- and narrow-ranged lineages of Causonis (Vitaceae) - Jinren Yu; Hong Zhao; Yanting Niu; Yichen You; Russell L. Barrett; Rindra Manasoa Ranaivoson; Romer Narindra Rabarijaona; Gaurav Parmar; Langxing Yuan; Xiaofeng Jin; Pan Li; Jianhua Li; et al. (BMC Biology, 2023)
Abstract Background Explaining contrasting patterns of distribution between related species is crucial for understanding the dynamics of biodiversity. Despite instances where hybridization and whole genome duplication (WGD) can yield detrimental outcomes, a role in facilitating the expansion of distribution range has been proposed. The Vitaceae genus Causonis exhibits great variations in species’ distribution ranges, with most species in the derived lineages having a much wider range than those in the early-diverged lineages. Hybridization and WGD events have been suggested to occur in Causonis based on evidence of phylogenetic discordance. The genus, therefore, provides us with an opportunity to for explore different hybridization and polyploidization modes in lineages with contrasting species’ distribution ranges. However, the evolutionary history of Causonis incorporating potential hybridization and WGD events remains to be explored. Results With plastid and nuclear data from dense sampling, this study resolved the phylogenetic relationships within Causonis and revealed significant cyto-nuclear discordance. Nuclear gene tree conflicts were detected across the genus, especially in the japonica-corniculata clade, which were mainly attributed to gene flow. This study also inferred the allopolyploid origin of the core Causonis species, which promoted the accumulation of stress-related genes. Causonis was estimated to have originated in continental Asia in the early Eocene, and experienced glaciation in the early Oligocene, shortly after the divergence of the early-divergent lineages. The japonica-corniculata clade mainly diversified in the Miocene, followed by temperature declines that may have facilitated secondary contact. Species distribution modeling based on current climate change predicted that the widespread C. japonica tends to be more invasive, while the endemic C. ciliifera may be at risk of extinction. Conclusions This study presents Causonis, a genus with complex reticulate evolutionary history, as a model of how hybridization and WGD modes differ in lineages of contrasting species’ geographic ranges. It is important to consider specific evolutionary histories and genetic properties of the focal species within conservation strategies.